„Geht hinaus in alle Milieu-Welten!“: Theologisches Modell für die Praxis der Kirche - Ritter, Klaus (European Journal of Mental Health, 2007)
“Go Forth to All Milieu Worlds!” A Theological Model for Church Practice: The article deals with the question of preaching, taking into consideration alienated social milieus. It describes the theological prerequisite based on which the modern world can be understood, and from which various action impulses originate. In relation to this it cites an idea of Klaus Hemmerle that describes preaching as a communications process between three important elements. It is made clear why encountering various milieus is necessary from the point of view of the self-evangelisation of the church.